Genome‐wide admixture mapping of DSM‐IV alcohol dependence, criterion count, and the self‐rating of the effects of ethanol in African American populations. Issue 3 (11th July 2020) - Lai, Dongbing; Kapoor, Manav; Wetherill, Leah; Schwandt, Melanie; Ramchandani, Vijay A.; Goldman, David; Chao, Michael; Almasy, Laura; Bucholz, Kathleen; Hart, Ronald P.; Kamarajan, Chella; Meyers, Jacquelyn L.; et al.
Abstract: African Americans (AA) have lower prevalence of alcohol dependence and higher subjective response to alcohol than European Americans. Genome‐wide association studies (GWAS) have identified genes/variants associated with alcohol dependence specifically in AA; however, the sample sizes are still not large enough to detect variants with small effects. Admixture mapping is an alternative way to identify alcohol dependence genes/variants that may be unique to AA. In this study, we performed the first admixture mapping of DSM‐IV alcohol dependence diagnosis, DSM‐IV alcohol dependence criterion count, and two scores from the self‐rating of effects of ethanol (SRE) as measures of response to alcohol: the first five times of using alcohol (SRE‐5) and average of SRE across three times (SRE‐T). Findings revealed a region on chromosome 4 that was genome‐wide significant for SRE‐5 ( p value = 4.18E‐05). Fine mapping did not identify a single causal variant to be associated with SRE‐5; instead, conditional analysis concluded that multiple variants collectively explained the admixture mapping signal. PPARGC1A, a gene that has been linked to alcohol consumption in previous studies, is located in this region. Our finding suggests that admixture mapping is a useful tool to identify genes/variants that may have been missed by current GWAS approaches in admixed populations.